Aging Workers and the Employee-Employer Relationship - Bal, P. Matthijs; Kooij, Dorien T.A.M; Rousseau, Denise M. (Springer International Publishing : Imprint: Springer, 2015)
This book focuses on the aging workforce from the employment relationship perspective. This innovative book specifically focuses on how organizations can ensure their aging workers remain motivated, productive, and healthy. In 15 chapters, several experts on this topic describe how organizations through effective human resource management can ensure that workers are able to continue working at higher age. In addition, this book discusses the role older workers themselves play in continuing work at higher age. To do this, the authors integrate research from different areas, such as literature on leadership, psychological contracts, and diversity with literature on the aging workforce. Through this integration this book provides innovative ways for organizations and workers to maintain productivity, motivation and health. Aging Workers and the Employee-Employer Relationship summarizes the latest research on how employment relationships change with age and its implications for supporting the well-being, motivation, and productivity of older workers. It identifies ways to improve how both companies and workers solve the problems they face. These include better designed employment practices and more adaptive job content and developmental opportunities for aging workers along with activities aging workers can engage to enhance their own job crafting, learning and employability.